Application of Random Forest Algorithm in Xijiang River Flood Forecasting - LIU Hechang; ZHAO Bohua; SUN Bo (Renmin Zhujiang)
Based on the measured flood data from 1952 to 2005 in Qianjiang Station,Liuzhou Station,and Wuxuan Station of Xijiang River,this paper selects the characteristic factors of flood forecasting by analyzing the correlation of flood flow at upstream and downstream stations.Meanwhile,the random forest algorithm is adopted to build a flood forecasting model for Wuxuan Station.The results are as follows.The certainty coefficients of the 12~48 h flood process in the studied station during the calibration period are more than 0.98 with the pass rates more than 98%.Additionally,the certainty coefficients of the 12~24 h flood process during the verification period are more than 0.72,with a pass rate of more than 82%.Thus,the proposed model has high forecast accuracy and little uncertainty and can provide a reference for flood forecasting methods.